2019
DOI: 10.1093/sp/jxz023
|View full text |Cite
|
Sign up to set email alerts
|

Inclusiveness of Parental-Leave Benefits in Twenty-One European Countries: Measuring Social and Gender Inequalities in Leave Eligibility

Abstract: This article analyzes eligibility for parental-leave benefits in twenty-one European countries. It distinguishes four ideal-type approaches to how leave-related benefits are granted (in-)dependent of parents’ labor market position: universal parenthood model, selective parenthood model, universal adult-worker model, and selective adult-worker model. An eligibility index is created to measure the inclusiveness of parental-leave benefits, alongside the degree of (de-)gendered entitlements. The importance of empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 28 publications
(56 reference statements)
0
87
0
3
Order By: Relevance
“…4 Eligibility may be conditioned by strict social security-insurance or employment-related criteria, citizenship, family type, etc. (see, for instance, McKay et al, 2016;Sainsbury, 2019;Dobrotić and Blum, 2019;Wong et al, 2019), influencing the leave take-up rates of different groups of parents within the country. 5 Brighouse and Wright (2008) recognize the need for a more nuanced elaboration of equalitypromoting leaves by distinguishing between a moderate and a radical version of equalitypromoting leaves, while arguing that these versions do not exist in any country.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Eligibility may be conditioned by strict social security-insurance or employment-related criteria, citizenship, family type, etc. (see, for instance, McKay et al, 2016;Sainsbury, 2019;Dobrotić and Blum, 2019;Wong et al, 2019), influencing the leave take-up rates of different groups of parents within the country. 5 Brighouse and Wright (2008) recognize the need for a more nuanced elaboration of equalitypromoting leaves by distinguishing between a moderate and a radical version of equalitypromoting leaves, while arguing that these versions do not exist in any country.…”
Section: Resultsmentioning
confidence: 99%
“…The focus here is on the leave policy development patterns and main policy concerns embedded in the leave policy design from a gender perspective. Recent findings legitimately point also to the social (i.e., class, ethnicity, new immigrant status) inequalities inherent to the leave policy design, with eligibility criteria being an important condition for take-up of paid leave by different social groups within a country (e.g., McKay et al, 2016;Sainsbury, 2019;Dobrotić and Blum, 2019). However, 1) the analysis of both the gender and social inequality dimensions of leave policy design goes beyond the scope of any one article; and 2) the historical data on eligibility criteria and how these are translated into take-up rates in the EFSCs are not available and reliable.…”
Section: Data and Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…14 When the Nordic countries extended leaves in the 1990s and 2000s, they did so by offering non-transferable and individual leaves for fathers (see Eydal and Rostgaard 2014 ). 15 In their study of 21 European countries, Dobrotić and Blum (2020 ) found that 15 of the 21 countries are embracing some version of a mixed system. 16 Other leave benefi ts offered by the federal government, with wage replacement rates of up to 55 percent of earnings to a maximum of $573/week, are the family caregiver benefi t for children, the family caregiver benefi t for adults, and the compassionate care benefi t for end-of-life care ( ESDC 2020 c).…”
Section: Notesmentioning
confidence: 99%